Leaking Heart: Ticking Time Bomb! - Marella, Punnaiah (Medknow Publications & Media Pvt Ltd, 2013)
CONTEXT: Cardiac rupture is a very important but under-recognized complication of acute myocardial infarction and usually happens within a week of the event. Sometimes it can be subacute and may not be typical of an acute blow out rupture. Hence careful evaluation is needed as a missed or delayed diagnosis can be fatal. An emergent echocardiogram may aid in immediate diagnosis. Surgery is the only treatment option and is mandatory despite the high mortality risk. CASE REPORT: An elderly male presented with dizziness and hypotension. Based on the timeline of his symptomatology, electrocardiographic abnormalities and labs, a subacute cardiac rupture was suspected in the emergency room itself. A high index of suspicion is needed to diagnose cardiac rupture. CONCLUSION: Subacute cases can be missed easily as presentation may not be dramatic. They can rapidly progress to a blowout rupture increasing mortality risk heavily even with surgical treatment.